1990
DOI: 10.1088/0031-8949/41/1/017
|View full text |Cite
|
Sign up to set email alerts
|

Ionic fragmentation of SiH4following theK-shell excitation

Abstract: Ionic fragmentation of SiH, has been studied in the vicinity of the Si : K-edge in the photon energy range 1800-1900eV. Ionic fragments observed at photon energies above the Si: Is * U* excitation are mostly atomic ions Siq+ (q = 1-3) and H + . Ratios of the abundances for Si+, and Si2+ and Si3+ are roughly 4: 4: I, and the abundance of H+ is much higher than the sum of the Si+, Si2+ and Si3+ abundances. The averaged kinetic energy release given to H+ is estimated to be about 12eV. This complete decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Bescos et al 7 studied photoionization and photofragmentation of large neutral silicon clusters using femtosecond laser pulses of ∼ 10 13 W/cm 2 and reported formation of Si 4+ ions having kinetic energies ∼ 500 eV. In yet another study, generation of multiply charged silicon ions was reported 8 upon Si K-shell excitation of SiH 4 using synchrotron radiation of ∼ 1.9 keV energy.…”
Section: Introductionmentioning
confidence: 99%
“…Bescos et al 7 studied photoionization and photofragmentation of large neutral silicon clusters using femtosecond laser pulses of ∼ 10 13 W/cm 2 and reported formation of Si 4+ ions having kinetic energies ∼ 500 eV. In yet another study, generation of multiply charged silicon ions was reported 8 upon Si K-shell excitation of SiH 4 using synchrotron radiation of ∼ 1.9 keV energy.…”
Section: Introductionmentioning
confidence: 99%
“…Although proton fragments were detected as well, we do not use them for the determination of the total charge state of the molecule, because typically more than one proton is ejected, and the total detection efficiency becomes very low for coincidences of more than three particles. Therefore, in order to estimate the total charge, we assume that all hydrogen fragments are charged, which is well justified for higher charge states [19], but might deviate considerably for lower ones. The deduced total charge for the methylselenol molecule is shown in Fig.…”
mentioning
confidence: 99%
“…The axial-recoil conditions are applicable to the photodissociation processes after both K-shell excitation and ionization, since the fragment ions are instantaneously emitted from a repulsive potential of molecular ions, which is reached by a fast Auger decay of the K-shell vacancy (τ ∼ 10 −14 s) compared to molecular rotation periods (τ ∼ 10 −10 s). Three groups have reported β parameter determinations for the firstrow diatomic molecules in the vicinity of the K-shell ionization thresholds based on the observation of photoions [45][46][47][48][49][50]. One of them (Saito and Suzuki [45,46,50]) resolved the time-of-flight (TOF) mass spectra of fragment ions at the magic angle into various kinetic energy components using a β value of 0.…”
Section: B Auger Electron and Fluorescence Angular Distributionsmentioning
confidence: 99%